Factors influencing digital entrepreneurship and role of Grameenphone to promote entrepreneurship in digital ecosystem - Moni, Bristy Das (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.